2018
DOI: 10.1302/0301-620x.100b1.bjj-2017-0605.r1
|View full text |Cite
|
Sign up to set email alerts
|

A functional comparison of medial pivot and condylar knee designs based on patient outcomes and parameters of gait

Abstract: This study corroborates a previous study by the same authors that showed equally good results in clinical outcome and gait between the conventional single radius and medial pivot designs under stringent testing conditions. Cite this article: 2018;(1 Supple A)100-B:76-82.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…Benjamin et al showed no difference between SR TKA and MP TKA, and Bae et al showed equivalent clinical outcomes between MR TKA and MP TKA. 33,34 On the other hand, Kim et al showed worse knee society scores and less satisfaction in MP TKA when compared to MR TKA. 35 In contrast, Hossain et al showed MP TKA had better range of movement, physical component of SF36, Total Knee Function Questionnaire and less pain on WOMAC subscale, 36 and Samy et al showed better forgotten knee scores in MP TKA.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Benjamin et al showed no difference between SR TKA and MP TKA, and Bae et al showed equivalent clinical outcomes between MR TKA and MP TKA. 33,34 On the other hand, Kim et al showed worse knee society scores and less satisfaction in MP TKA when compared to MR TKA. 35 In contrast, Hossain et al showed MP TKA had better range of movement, physical component of SF36, Total Knee Function Questionnaire and less pain on WOMAC subscale, 36 and Samy et al showed better forgotten knee scores in MP TKA.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…According to Papagiannis et al 's kinematic and kinetic analysis, 21) early outcomes could not demonstrate any notable functional and wear advantages between the two groups. Likewise, Benjamin et al 's study 20) revealed comparable functional grades for both PS and MP groups. However, a level I RCT by Kim et al 18) showed strong preferences for the non-MP implants as they obtained smaller ranges of knee motion, less patient satisfaction (Hospital for Special Surgery Score, p = 0.023), and a higher complication rate in fixed bearing MP prostheses in their early outcome, despite similar long-term fixation and survival rates of both MP and PFC Sigma prostheses in their subsequent report.…”
Section: Discussionmentioning
confidence: 79%
“…As far as MP total knee arthroplasty is concerned, there are limited studies comparing its outcomes with those of other implant designs (Table 3). 5,13,[18][19][20][21][22][23][24][25] To date, there is only one randomized study by Hossain et al, 5) which has compared outcomes of an MP knee to a fixed-bearing multi-radius PS implant. There are three other randomized controlled trials (RCTs), which have compared an MP design to a mobile PS knee: an ultra-congruent rotating platform knee in studies by Kim et al 18) and Kim et al 19) and a single radius knee in a study by Benjamin et al 20) There are a few more matched pair studies and case series, which have looked at outcomes of the MP design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing on these knowledge, the conceptualization of a new medial pivot prosthesis design took place only in 1994 with the Freeman–Samuelson model. 21 22 A medial pivot knee system was developed to address residual pain and the patient's desire for fully restored anatomical function after total knee replacement. 23 An increased stability of the implants was observed throughout the entire range of motion 24 guaranteed by a “ball-and-socket” articulation of the medial tibiofemoral compartment, and a reduction of polyethylene wear with no additional fixation problems.…”
Section: Borelli's Unrecognized Contribution In Total Knee Arthroplastymentioning
confidence: 99%